Research of Capacitance Voltage Balance Strategies for MMC - WANG Xiyan (Kongzhi Yu Xinxi Jishu)
In order to achieve capacitance voltage balance of modular multilevel converter(MMC), it analyzed the components of the leg current, and then the quasi proportional resonance controller (PRC) was adopted to improve the inner loop tracking performance of voltage balance control based on the proportional plus integral(PI). At last, the simulation was carried out to verify this algorithm ability.